Study of Cu Electrochemical Polishing Mechanism With Observation of Water Acceptor Diffusion - Park, Kimoon; Lee, Jinhyun; Kim, Youjung; Yoon, Sangwha; Yoo, Bongyoung (Frontiers in Chemistry, 2021)
The salt-film and water acceptor mechanisms were generally accepted mechanisms for Cu electrochemical polishing (ECP) theory. These mechanisms of Cu ECP are still controversial for a long time. Conventional and new electrochemical analysis methods were used to investigate the mechanisms and behaviors of Cu electrochemical polishing. Two cases of Cu dissolution, with and without polishing, were classified by results of linear scan voltammetry (LSV) and scanning electron microscopy (SEM). The electrochemical impedance spectroscopy (EIS) showed results the main difference in these two cases was in the low-frequency region. However, it was hard to distinguish between the salt-film and water acceptor mechanisms by conventional electrochemical analysis. A scanning electrochemical microscopy (SECM) system, a new electrochemical analysis method that measures the electrolysis currents of the water acceptors along with a set distance from the substrate, was used to investigate the Cu ECP mechanism. Accordingly, the diffusion of the water acceptors was successfully confirmed for the first time. Finally, the mechanisms of the Cu ECP are definitively described by using all analysis results.